A comprehensive industrial practice for Industrial Internet Platform (IIP): General model, reference architecture, and industrial verification. (August 2021) - Zhang, Xianyu; Ming, Xinguo
Highlights: A general model for IIP from an industrial practice survey is proposed. A system model for IIP using system engineering analysis is proposed. Related reference subsystems for IIP are proposed. The detailed industrial verification for IIP is given. It has a certain reference value for industry and government. Abstract: With the upgrading of industrial era, the rise of industrial Internet environment and the development of intelligent technology, enterprises will pay more attention to the system platform, information sharing, network collaboration, personalized customization and recommendation of services when designing, implementing and operating an industrial information platform, which is called Industrial Internet Platform (IIP). In the existing literature, scholars focus on a local dot, such as: technology, function, elements and application based on IIP. However, there is a lack of an overall framework to study the top-level planning of IIP implementation from a systematic perspective. Moreover, there are few studies on the detailed path and steps of IIP implementation in a specific industry. The research objective is to study the general model, reference architecture, service evaluation index system, implementation path, application verification, etc. for IIP which meets the needs of industry on the basis of existing theory and industrial practice, and to provide reference for government and industry planning, design, implementation and promotion of IIP. From a case study, the comprehensive performance rate of comprehensive ability for IIP in a pharmaceutical manufacturing industry enterprise is calculated. It can reflect the comprehensive ability for IIP in enterprise from the ability of the IIP's resource management, platform technology, industrial application, and etc. In addition, the general model, reference architecture, implementation path and service evaluation system of IIP can improve the enterprise's resource management ability, platform service ability, industrial application ability, and enhance the core value of the enterprise and increase benefits.